Case report: Primary subcutaneous Rosai-Dorfman-Destombes of the scalp with intra-cranial involvement: diagnosis and treatment of a rare case with literature review - Zhenwei, Qin; Beiyan, Tang; Ding, Chen; Qiang, Liang; Qiang, Dong; Huixia, Zhai; Wei, Kang; Xianjun, Zhao; Yawen, Pan (Frontiers in Neurology, 2025)
Rosai-Dorfman-Destombes disease (RDD) is a rare histiocytic proliferative disorder, with primary scalp and intracranial involvement being particularly uncommon. The imaging features and clinical manifestations of RDD often overlap with other intracranial lesions, such as meningiomas, leading to misdiagnosis. This study presents a case of primary scalp and intracranial RDD, with a comprehensive analysis of its imaging, pathological, and intraoperative findings, alongside a review of the literature on central nervous system (CNS) RDD and its diagnostic and therapeutic advancements. Preoperative CT and MRI scans clearly depicted characteristic changes in the scalp and intracranial lesions. However, the preoperative assessment failed to fully recognize abnormalities in the skull base, leading to an incomplete initial understanding. During surgery, the dura mater and obstructed superior sagittal sinus were resected extensively, and the pathology confirmed RDD. Postoperative recovery was smooth, and no recurrence was observed during follow-up. This case emphasizes the importance of detailed imaging in the diagnosis and treatment of RDD, combining preoperative evaluation with intraoperative observations to reduce the risk of misdiagnosis and recurrence. Furthermore, the exploration of individualized treatment strategies and targeted therapies plays a crucial role in managing complex cases. This study offers valuable experience for the diagnosis and treatment of similar rare cases.